Hierarchically structured superhydrophobic flowers with low hysteresis of the wild pansy (Viola tricolor) – new design principles for biomimetic materials - Schulte, Anna J.; Droste, Damian M.; Koch, Kerstin; Barthlott, Wilhelm (Beilstein Journal of Nanotechnology, 2011)
Hierarchically structured flower leaves (petals) of many plants are superhydrophobic, but water droplets do not roll-off when the surfaces are tilted. On such surfaces water droplets are in the “Cassie impregnating wetting state”, which is also known as the “petal effect”. By analyzing the petal surfaces of different species, we discovered interesting new wetting characteristics of the surface of the flower of the wild pansy (Viola tricolor). This surface is superhydrophobic with a static contact angle of 169° and very low hysteresis, i.e., the petal effect does not exist and water droplets roll-off as from a lotus (Nelumbo nucifera) leaf. However, the surface of the wild pansy petal does not possess the wax crystals of the lotus leaf. Its petals exhibit high cone-shaped cells (average size 40 µm) with a high aspect ratio (2.1) and a very fine cuticular folding (width 260 nm) on top. The applied water droplets are in the Cassie–Baxter wetting state and roll-off at inclination angles below 5°. Fabricated hydrophobic polymer replicas of the wild pansy were prepared in an easy two-step moulding process and possess the same wetting characteristics as the original flowers. In this work we present a technical surface with a new superhydrophobic, low adhesive surface design, which combines the hierarchical structuring of petals with a wetting behavior similar to that of the lotus leaf.
Keywords: anti-adhesive; petal effect; petal structures; polymer replication; superhydrophobic

(untitled) - Koch, K.; Bhushan, B.; Barthlott, W. (Prog. Mater. Sci., 2009)

(untitled) - Bargel, H.; Koch, K.; Cerman, Z.; Neinhuis, C. (Funct. Plant Biol., 2006)

Tropische und Subtropische Pflanzenwelt - Barthlott, W.; Ehler, N. (Steiner, 1977)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Neinhuis, C.; Barthlott, W. (Ann. Bot. (Oxford, U. K.), 1997)

(untitled) - Koch, K.; Barthlott, W. (Philos. Trans. R. Soc. London, Ser. A, 2009)

(untitled) - Barthlott, W.; Schimmel, T.; Wiersch, S.; Koch, K.; Brede, M.; Barczewski, M.; Walheim, S.; Weis, A.; Kaltenmaier, A.; Lederer, A.; Bohn, H. F. (Adv. Mater., 2010)

Functional Surfaces in Biology - Cerman, Z.; Striffler, B. F.; Barthlott, W. (Springer, 2009)

(untitled) - Roach, P.; Shirtcliffe, N. J.; Newton, M. I. (Soft Matter, 2008)

(untitled) - Barthlott, W.; Wollenweber, E. (Tropische und subtropische Pflanzenwelt, 1981)

(untitled) - Wenzel, R. N. (Ind. Eng. Chem., 1936)

(untitled) - Cassie, A. B. D.; Baxter, S. (Trans. Faraday Soc., 1944)

(untitled) - Lafuma, A.; Quéré, D. (Nat. Mater., 2003)

Fundamentals of adhesion and interfaces - Israelachvili, J. N.; Chen, Y.-L.; Yoshizawa, H. (VSP, 1994)

(untitled) - Extrand, C. W. (Langmuir, 2002)

(untitled) - Wang, S.; Jiang, L. (Adv. Mater., 2007)

(untitled) - Feng, L.; Zhang, Y.; Xi, J.; Zhu, Y.; Wang, N.; Xia, F.; Jiang, L. (Langmuir, 2008)

(untitled) - Ensikat, H. J.; Schulte, A. J.; Koch, K.; Barthlott, W. (Langmuir, 2009)

(untitled) - Hong, X.; Gao, X.; Jiang, L. (J. Am. Chem. Soc., 2007)

(untitled) - Liu, M.; Zheng, Y.; Zhai, J.; Jiang, L. (Acc. Chem. Res., 2010)

Springer Handbook of Nanotechnology - Bhushan, B.; Jung, Y. C.; Nosonovsky, M. (Springer, 2010)

(untitled) - Shi, F.; Chen, X.; Wang, L.; Niu, J.; Yu, J.; Wang, Z.; Zhang, X. (Chem. Mater., 2005)

(untitled) - Xi, J.; Jiang, L. (Ind. Eng. Chem. Res., 2008)

(untitled) - Bormashenko, E.; Stein, T.; Pogreb, R.; Aurbach, D. (J. Phys. Chem. C, 2009)

(untitled) - Bhushan, B.; Her, E. K. (Langmuir, 2010)

(untitled) - Xia, Y.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Koch, K.; Dommisse, A.; Barthlott, W.; Gorb, S. N. (Acta Biomater., 2007)

(untitled) - Koch, K.; Schulte, A. J.; Fischer, A.; Gorb, S. N.; Barthlott, W. (Bioinspir. Biomim., 2008)

(untitled) - Schulte, A. J.; Koch, K.; Spaeth, M.; Barthlott, W. (Acta Biomater., 2009)

(untitled) - Whitney, H.; Kolle, M.; Alvarez-Fernandez, R.; Steiner, U.; Glover, B. J. (Commun. Integr. Biol., 2009)

(untitled) - Zhang, Y.; Hayashi, T.; Inoue, M.; Oyama, Y.; Hosokawa, M.; Yazawa, S. (Acta Hort. (ISHS), 2008)

(untitled) - Kevan, P. G.; Lane, M. A. (Proc. Natl. Acad. Sci. U. S. A., 1985)

(untitled) - Callies, M.; Quéré, D. (Soft Matter, 2005)

(untitled) - Sun, C.-H.; Gonzalez, A.; Linn, N. C.; Jiang, P.; Jiang, B. (Appl. Phys. Lett., 2008)

(untitled) - Nosonovsky, M.; Bhushan, B. (Ultramicroscopy, 2007)

(untitled) - Bhushan, B.; Jung, Y. C.; Koch, K. (Philos. Trans. R. Soc., A, 2009)

Untersuchungen zum Einfluss von Struktur und Chemie auf die Benetzbarkeit und die Selbstreinigung superhydrophober Oberflächen - Fürstner, R. (Shaker Verlag, 2002)

(untitled) - Koch, K.; Dommisse, A.; Niemietz, A.; Barthlott, W.; Wandelt, K. (Surf. Sci., 2009)